Analisis Efektivitas Sistem Pengendalian Internal pada Divisi Personalia : (Studi Kasus PT. Sendang Derma Pesona) - Ivan Erlangga; Ika Ismatul Hawa; Miftha Aulia Rahma; Naysya Indriamy; Eka Indah Trisnawati; Silvia Athikasuri; Dirvi Surya Abbas (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2026)
This study aims to analyze the effectiveness of the internal control system in the Personnel Division of PT Sendang Derma Pesona in supporting effective, efficient, and well-governed human resource management. The background of this research is based on the importance of internal control systems in preventing administrative errors, reducing the risk of fraud, and ensuring compliance with labor regulations, particularly in personnel and payroll functions. This study employs a descriptive qualitative approach using an operational audit method. Data were collected through questionnaires, interviews, and document observation covering recruitment procedures, personnel data management, employee transfers, authorization processes, as well as payroll and bank reconciliation procedures. The results indicate that, in general, the internal control system in the Personnel Division has been implemented adequately, as reflected by complete personnel documentation and multi-level authorization in decision-making processes. However, several weaknesses were identified, including the lack of proper segregation of duties between payroll preparation and salary payment, the absence of regular bank reconciliation, and the continued use of manual personnel archive management. These weaknesses indicate that the internal control system still needs to be strengthened to minimize the risk of errors and improve the efficiency of personnel administration. The findings of this study are expected to provide practical implications for management in improving internal control policies and procedures to support better corporate governance and sustainable organizational performance.